2019
DOI: 10.3171/2019.7.peds19188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of children with radiation-induced cerebral vasculopathy

Abstract: OBJECTIVEStenoocclusive cerebral vasculopathy is an infrequent delayed complication of ionizing radiation. It has been well described with photon-based radiation therapy but less so following proton-beam radiotherapy. The authors report their recent institutional experience in evaluating and treating children with radiation-induced cerebral vasculopathy.METHODSEligible patients were age 21 years or younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…None has had a post-EDAS stroke. These results, combined with the results of Hersh et al [16], support consideration of the PAA for indirect revascularization procedures in children and adolescents when the STA is not a suitable candidate or when an additional donor artery is desired.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…None has had a post-EDAS stroke. These results, combined with the results of Hersh et al [16], support consideration of the PAA for indirect revascularization procedures in children and adolescents when the STA is not a suitable candidate or when an additional donor artery is desired.…”
Section: Discussionsupporting
confidence: 63%
“…Ten hemispheres in this study underwent PAA EDAS, and the authors found similar Matsushima grades [15] in patients who underwent PAA versus STA EDAS. In addition, Hersh et al [16] reported use of the PAA for indirect revascularization in 2 pediatric patients with radiation-induced cerebral vasculopathy as part of a larger study in which various external carotid branches, including the STA and OA, were used; they reported robust collateralization formation at 1 year post-surgery, with no post-surgical infarctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are limited for antithrombotic therapy for secondary stroke prevention in children and are mostly extrapolated from adults. Antiplatelet therapy is recommended for patients with moyamoya disease 73,76,77 . Surgical revascularization is considered in patients with clinical symptoms concerning for transient ischemic attacks or strokes, chronic subclinical ischemia, progressive vasculopathy, and high-grade vascular stenosis 76,77 .…”
Section: Long-term Outcomes and Neurotoxicity From Treatmentmentioning
confidence: 99%
“…73,76,77 Surgical revascularization is considered in patients with clinical symptoms concerning for transient ischemic attacks or strokes, chronic subclinical ischemia, progressive vasculopathy, and high-grade vascular stenosis. 76,77 Current recommendations for brain tumor survivors who have received RT include yearly neurologic examinations and brain MRI with DWI and MR angiography (MRA) as clinically indicated. 78,79 Radiation necrosis can be seen as early as immediately after completion of RT but can also present years later.…”
Section: Radiation Therapymentioning
confidence: 99%